Scientific Calculators and the Skill of Efficient Computation - Yasin, Mohd Yusuf (BIBECHANA, 2012)
Calculators are part and parcel of modern education. Involvement of science and engineering in different fields of knowledge is increasing with each bit of time is passed by, and they are playing a role in description and characterization of the delicate phenomena of nature arising day by day. These fields of knowledge and mathematics in particular, are influencing even those distant branches of knowledge, which were so far imagined to be free of mathematics. Even art is not free of mathematics and there exists mathematical art. Computations are getting lengthy and complex specially in design and analysis of engineering systems. Scientific calculators are handy tools. But an efficient computation is a skill that can be developed. Keywords: scientific calculators; calculator techniques; efficient computation; efficient use of calculators, computation skills; numerical techniques DOI: http://dx.doi.org/10.3126/bibechana.v8i0.4702 BIBECHANA 8 (2012) 31-36